Badania kinetyczne procesu denitryfikacji z dawkowaniem zewnętrznego źródła węgla z postaci produktów odpadowych z produkcji alkoholu = Kinetic investigations of denitrification with the addition of external carbon sources in the form of byproducts from alcohol production - Kaszubowska, Magdalena; Majtacz, Joanna; Mąkinia, Jacek; Czerwionka, Krzysztof; Kulbat, Eliza (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study was evaluation of the feasibility of using byproducts from alcohol production (fusel oils) as an alternative carbon source for denitrification. For comparison, the settled wastewater (without further pretreatment and after coagulation-floculation) as well as two conventional external carbon sources (ethanol and acetic acid) were also investigated.
Keywords: denitryfikacja; osad czynny; usuwanie azotu; źródła węgla; denitrification; activated sludge; nitrogen removal; carbon sources